2011
DOI: 10.1680/stbu.10.00010
|View full text |Cite
|
Sign up to set email alerts
|

Development of prefabricated timber–concrete composite floor systems

Abstract: The timber-concrete composite structure consists of timber joists or beams effectively interconnected to a concrete slab cast on top of the timber members. This type of structure is finding new applications in multi-storey buildings and short-span bridges. Most of the research performed to date has focused on systems where 'wet' concrete is cast on top of timber beams with mounted connectors. This paper presents a novel composite system where the concrete slab is prefabricated off-site with connectors already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
0
21
1
Order By: Relevance
“…The analytical solution is given in Eq. (6). Frequency coefficient, C B , is the same for both pin-pin and pin-roller boundary conditions whereas higher frequency is expected for pin-pin compared to pin-roller boundary condition.…”
Section: Wyatt (1989)mentioning
confidence: 84%
See 1 more Smart Citation
“…The analytical solution is given in Eq. (6). Frequency coefficient, C B , is the same for both pin-pin and pin-roller boundary conditions whereas higher frequency is expected for pin-pin compared to pin-roller boundary condition.…”
Section: Wyatt (1989)mentioning
confidence: 84%
“…The investigation was conducted based on the natural period, mode shapes and effective damping of the flooring systems. Fragiacomo and Lukaszewska [6] assessed vibration performance of the TCC flooring systems, where the concrete slab was prefabricated off-site with connectors and connected to the timber joists on site, using the natural frequencies and damping ratios of the flooring systems. This paper presents the results from dynamic experimental investigations on four TCC beams with identical geometry and with different connection systems.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, secant stiffness is deducted from standardized tests and analysed according to NF EN 26891 standard. Some authors (Ceccotti 1995;Fragiacomo and Lukaszewska 2011;Lukaszewska 2009) showed that depending on connector type, stiffness by standardized approach could lead to significant deviation in design value. Numerical and experimental studies are proposed in order to understand the behaviour of multi-layer beams, focusing on stiffness adapted values.…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of this system include improved airborne sound transmission compared to timber floors, owing to the increased mass and improved load-carrying capacity (Ceccotti, 2002;Fragiacomo, 2012). Although many researchers have commented that the addition of a concrete topping also improves the vibration performance of timber floors (Ceccotti, 1995;Deam et al, 2007;Fragiacomo and Lukaszewska, 2011;Steinberg et al, 2003), relatively little is known about how the vibration response of a timber floor changes with the addition of a topping. This is despite the vibration performance governing some timber-concrete composite floor designs (Toratti and Kevarinmäki, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…0% to 7 . 5% in testing, depending on type and spacing of connectors and whether prefabricated or cast-in-situ concrete slabs were assessed (Fragiacomo and Lukaszewska, 2011;Ghafar et al, 2008;Rijal et al, 2011).…”
mentioning
confidence: 99%